Outcome of Novel Treatment of Thyroid Gland in Patients with Advance Carcinoma Larynx - Hasnain Haider, Bakht Aziz, Umair Wahab, Atiq U Rehman, Zahra Aleem, Maryam Umar, Irshad Malik, Kashif Iqbal Malik (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Among the carcinomas Head and Neck surgeon encounter, carcinoma larynx is amongst the most commons. Thyroid gland is close to larynx so is its risk to be involved by laryngeal malignancies. Removing whole or part of thyroid gland may put the patient at risk of permanent or temporary hypothyroidism and hypoparathyroidism. In recent past a number of risk factors are nominated to predict invasion of thyroid gland by laryngeal malignancies. So, there is a need to re-consider the management of thyroid gland in total laryngectomy. Aim: To justify the management of thyroid gland in advance carcinoma larynx. Study design: The study is cross sectional Randomized Control Trial. Place and duration of study: We conducted this study in ENT Unit I of Jinnah Hospital Lahore from June 2021 to May 2022. Methodology: A total of 20 patients were included in this study and were randomly divided into two groups on the basis of management of thyroid gland. Group A underwent hemi thyroidectomy while thyroid sparing total laryngectomy was done in group B. Histological evaluation of thyroid Gland was done in group A in addition to analysis of local recurrence in both Groups. Mean duration of follow-up was 6 months. Data analysis was done by using SPSS software and is presented in tabulated forms as percentages. Results: The study showed that thyroid gland was not involved in all cases of advance laryngeal malignancies thus obviating the need of total or hemithyroidectomy in all patients with advance Squamous Cell Carcinoma Larynx. Practical implication: All the cases of advance laryngeal malignancies used to undergo total or at least hemithyroidectomy as bystander of total laryngectomy. This study helps the surgeon decide whether a patient with proven laryngeal malignancy needs thyroid gland manipulation or not, thus decreasing the morbidity of the patient and improving cost effectiveness. Conclusion: This study made us reach to the conclusion that in patients with Grade I and II SCC, with no clinical or radiological involvement of thyroid and cricoid cartilage, thyroid gland, strap muscles or skin, there is no need for manipulation of thyroid gland in patients undergoing total Laryngectomy. Keywords: Laryngeal Carcinoma, Thyroid Gland management, Total Laryngectomy with Hemi thyroidectomy,